Revisit Intention Model of Indonesian Consumers to Malaysia for Medical Tourism: An Extension of Theory Of Planned Behavior - ., Selwendri; Raharja, Sam’un Jaja; Hermanto, Bambang; Tresna, Pratami Wulan (Journal of Ecohumanism, 2024)
This study analyzes the factors influencing Indonesian consumers' revisit intention to Malaysia for medical tourism, using an extension of the Theory of Planned Behavior (TPB) integrated with additional variables such as perceived value, destination image, and customer satisfaction. Using a quantitative approach, data was collected through questionnaires distributed to 385 North Sumatra and Riau respondents who have done medical tourism to Malaysia. Data analysis was conducted using the Structural Equation Modeling (SEM) method using Partial Least Squares (PLS). The results showed that behavioral, normative, and control beliefs significantly affect attitude, subjective norms, and perceived behavioral control. Perceived value and destination image significantly affect customer satisfaction, while subjective norm, perceived behavioral control, and customer satisfaction significantly affect revisit intention. Attitude does not show a significant effect on revisit intention. Customer satisfaction effectively mediates perceived value/destination image and revisits intention. The findings provide insights for medical tourism service providers in Malaysia and policymakers in developing strategies to attract and retain medical tourists from Indonesia.